(untitled) (Research, Society and Development, 2024)
Diabetes Mellitus is a chronic non-communicable disease manifested, above all, by the elevation of serum glycemia, and its treatment consists of lifestyle changes combined with pharmacological therapies. From this perspective, complementary integrative treatments have been evaluated as complementary strategies in glycemic control, with Momordica charantia standing out for its hypoglycemic effects. That said, the present study aimed to identify the effects of Momordica charantia linked to hypoglycemia and systemic metabolic regulation as an adjuvant complementary therapy for Diabetes Mellitus. The review was carried out in the PubMed, Medline and ScienceDirect databases using the DeCS: “Momordica charantia” and “Diabetes Mellitus”, linked by the Boolean operator “AND”, resulting in 25 articles for analysis. The studies report satisfactory results regarding the hypoglycemic effects of Momordica charantia through varied mechanisms, such as stimulating the use of glucose, activating GLP-1, suppressing enzymes involved in gluconeogenic pathways, inhibiting intestinal uptake, as well as improving sensitivity. insulin and decreased lipid accumulation in the liver. In addition to its hypoglycemic effect, research carried out with diabetic mice also reports possible renal, hepatic and anti-inflammatory benefits. Furthermore, it was observed that Momordica charantia has compounds that help balance metabolism and can be considered as a therapeutic adjuvant for Diabetes Mellitus. However, more studies are still needed to identify more precisely the components of the herbal medicine and the side effects of its use.